Indigenous Antinuclear Literary Resistance: Jim Northrup’s Satire and Anishinaabe Trans/nationalism - Kyoko Matsunaga (Journal of Transnational American Studies, 2020)
“Indigenous Antinuclear Literary Resistance: Jim Northrup’s Satire and Anishinaabe Trans/nationalism” examines the way Jim Northrup (1943–2016), an Anishinaabe writer from the Fond du Lac Band of Lake Superior Chippewa in northern Minnesota, engages Anishinaabe trans/nationalism as he combats nuclear colonialism in his satirical columns. The fundamental nature of Anishinaabe trans/nationalism, described by Joseph Bauerkemper and Heidi Kiiwetinepinesiik Stark in “Trans/National Terrain of Anishinaabe Law and Diplomacy,” forms the basis of Northrup’s resistance to nuclear colonialism as he critiques the nuclear power plant and radioactive waste threatening the Mdewakanton Dakota residents of the Prairie Island Indian Community. He adds another layer to the politics of Indigenous trans/nationalism when he ridicules plans to send the radioactive waste from Prairie Island to be stored on the land of other Indigenous nations such as the Western Shoshone and Mescalero Apache. On another level, by emphasizing the bonds between Anishinaabe people in the United States and Canada, Northrup implies that Anishinaabe nationhood precedes the borders of nation states, defying the ideology of “transnational” in a conventional sense. With Indigenous trans/nationalism at the center of its argument, this essay considers Northrup’s use of satire and humor as an atomic age strategy to manifest Anishinaabe nationhood as well as to establish transnational Indigenous alliances to combat nuclear colonialism. Northrup situates his antinuclear opposition as part of an enduring multilateral Indigenous resistance to settler colonialism, and, in so doing, he emphasizes the importance of exercising treaty rights and insisting on the inherent sovereignty of the Anishinaabe people.